Strategi di Pasar Modal Syariah - Devara Rustiana; Sarah Ramadhani (Universitas Muhammadiyah Enrekang, 2022)
Capital market is market for longtherm money instrument. Sharia Capital Market is all activities in the capital market that do not conflict with Islamic principles. The Indonesian Islamic capital market is part of the Islamic finance industry which is regulated by the Financial Services Authority (OJK), in particular the directorate of the Islamic capital market. This journal describes the benefits of capital market instruments, risks, and strategies in the capital market.